2015
DOI: 10.1088/0004-637x/803/1/12
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Strontium and Barium Isotopic Compositions of Acid-Cleaned Single Mainstream Silicon Carbides From Murchison

Abstract: We present strontium, barium, carbon, and silicon isotopic compositions of 61 acidcleaned presolar SiC grains from Murchison. Comparison with previous data shows that acid washing is highly effective in removing both strontium and barium contamination. For the first time, by using correlated 88 Sr/ 86 Sr and 138 Ba/ 136 Ba ratios in mainstream SiC grains, we are able to resolve the effect of 13 C concentration from that of 13 C-pocket mass on s-process nucleosynthesis, which points towards the existence of lar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
126
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(140 citation statements)
references
References 80 publications
14
126
0
Order By: Relevance
“…Also the 13 C abundance inside the reservoir must be different than commonly inferred previously, remaining rather flat and at a low concentration over most of the pocket mass. These indications become now general constraints that must be taken into account by any mixing model aiming at producing an adequate reservoir of 13 C. In fact, as we shall see in the next Sections, our suggestions for the mixing of protons into the He-rich zone at TDU yield a partially-mixed layer that has the general characteristics suggested by Liu et al (2015). Basically, the papers quoted so far, although not adopting a specific physical model, derived from their exploratory approach convincing constraints on their parameters, which must now be repoduced by any further modelling.…”
Section: Constraints On the Main Neutron Source In Agb Starsmentioning
confidence: 66%
See 3 more Smart Citations
“…Also the 13 C abundance inside the reservoir must be different than commonly inferred previously, remaining rather flat and at a low concentration over most of the pocket mass. These indications become now general constraints that must be taken into account by any mixing model aiming at producing an adequate reservoir of 13 C. In fact, as we shall see in the next Sections, our suggestions for the mixing of protons into the He-rich zone at TDU yield a partially-mixed layer that has the general characteristics suggested by Liu et al (2015). Basically, the papers quoted so far, although not adopting a specific physical model, derived from their exploratory approach convincing constraints on their parameters, which must now be repoduced by any further modelling.…”
Section: Constraints On the Main Neutron Source In Agb Starsmentioning
confidence: 66%
“…For the rest, they found that purely stellar and Galactic observational data can be fitted, with different combinations of the parameters, by rather different choices of the 13 C reservoir. If confirmed, this indication would emphasize even more the relevance of presolar SiC data and of the Liu et al (2014a), Liu et al (2014b) and Liu et al (2015) analysis in informing us on otherwise inaccessible details of the mixing required for driving s-processing.…”
Section: Constraints On the Main Neutron Source In Agb Starsmentioning
confidence: 83%
See 2 more Smart Citations
“…In this contribution we shall in particular consider the approach by [22] that was already shown to be able to produce extended 13 C reservoirs and to induce neutron captures capable of reproducing not only the solar-system distribution of s-elements, but also the more stringent constraints [27][28][29] that are posed by the isotopic composition of presolar SiC grains: see e.g. [30].…”
Section: Introductionmentioning
confidence: 99%